Innovative Production Strategies for High-Quality, Traditional Pig Products - Martelli, Giovanna; Nannoni, Eleonora (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
In a number of European countries (e.g., Spain, Italy, France, Portugal, Slovenia, Croatia, Poland), a portion of the pig sector is aimed at the production of traditional and certified products (e.g., PDO-Protected Designation of Origin, PGI-Protected Geographical Indication). Dry-cured ham is probably the most famous traditional pork product; however, typical pork products are produced in (and exported to) many countries worldwide. The meat used for producing these high-quality delicacies needs to be suitable for seasoning and dry-curing, and these characteristics are the result of complex interactions between the animal (breed, genotype, rearing condition, feeding regime, age and weight at slaughter, etc.) and the environment, without disregarding the importance of ethical attributes such as animal welfare and the environmental impact.This Special Issue focuses on all the innovative production strategies for pigs intended for high-quality, typical productions (in term of higher sustainability of the whole production chain, improvement of animal welfare, innovative feeding and farming techniques, reduction in environmental impact, improvement in meat and fat quality, etc.), with emphasis on PDOs, PGIs, and other recognized production schemes, and it is aimed at providing new insights for a wide range of stakeholders from different countries.